An efficient Rhizobium rhizogenes-mediated transformation system for Cuscuta campestris - K. M. Asha Alles; P. G. L. T. Dilhani; C. H. W. M. R. Bhagya Chandrasekera; Pradeepa C. G. Bandaranayake (PLoS ONE, 2025)
Parasitism has evolved independently in various plant families, with Cuscuta campestris (field dodder) being an economically significant example. Despite advances in genomics and transcriptomics, functional studies in C. campestris are limited by the lack of an efficient genetic transformation system. This study introduces a highly effective Rhizobium rhizogenes-mediated transformation system for C. campestris using a pBIN plasmid harboring a Yellow Fluorescence Protein reporter gene. We optimized transformation and regeneration by assessing explant type, media composition, and plant growth regulators. Notably, host plant contact was essential for transgenic shoot regeneration. Over 70% transformation efficiency was achieved using cuttings co-incubated with modified Murashige and Skoog medium and 5 mg/L Benzylaminopurine, followed by transfer to tomato hosts. Additionally, we developed a complete in-vivo protocol over 30% regeneration efficiency. Transgenic shoots were confirmed for rol gene expression and haustoria formation, advancing functional studies in C. campestris.